Multimedia Development Using Visual Basic for Application (VBA) to Improve Students’ Learning Motivation in Studying Mathematics of Economics - Siti Nurul Hasana; Alifiani Alifiani (Universitas Tidar, 2019)
For Mathematics Education Study Program, Mathematics of Economics is a subject where Mathematics is applied in Economics. In this course, mathematical concepts and theories which have been studied in the previous semesters have to be applied in Economics that is new for the students. For this kind of subject, the lecturer has to be more creative in the class so that the lesson will be more interesting and understandable. The aim of this research is to know the improvement of learning motivation in Mathematics of Economics through the use of multimedia development using Visual Basic for Application (VBA) in the class. This multimedia is presented in the form of a game in Microsoft PowerPoint (PPt) program. Respondents of this study were 34 students of class A in the fourth semester of Mathematics Education study program of Teacher Training and Education Faculty at Universitas Islam Malang who were taking this course. This study uses a qualitative descriptive approach with data collection techniques using observation and interview techniques. The observation sheet and the interview guidelines used here are arranged based on indicators measuring learning motivation. The result shows that the use of multimedia development with VBA can improve the students’ learning motivation to study Mathematics of Economics. The recalling of mathematical concepts and theories which have been studied before can be more interesting in the form of a game, while the new Economics concepts and theories with the mathematical application inside can be understood easily in the form of competition that enhances the motivation.